A Framework for Planning for High-Volume High-Acuity Traumatic Mass Casualty Incidents. Issue Volume 34:Issue s1(2019) (May 2019) - Maslanka, Meghan; Mouille, Ann; Aiken, James; Elder, Jeffrey
Abstract : Introduction: In response to the Pulse Nightclub and Las Vegas mass shootings, staff from our Emergency Department (ED) at University Medical Center New Orleans designed a mass casualty incident (MCI) protocol aimed at preparing the entire hospital for high-volume, high-acuity incidents of unprecedented proportions. As we researched this effort, we discovered that no publically available framework currently exists to assist hospitals with creating their own comprehensive, functional MCI protocol. Aim: To develop a framework to assist hospitals with creating MCI plans tailored to fit the needs of their individual facility. Methods: Our hospital spent several years creating and refining an MCI protocol that is both comprehensive in addressing each service's needs and efficient for the staff expected to use it. Upon achieving the desired outcome of a well-functioning and tested protocol, the main contributors of the project met to create a consensus document on how we would approach the task with the benefit of hindsight. Results: Our document is meant to serve as a framework for hospitals looking to build their own plan. It is not a template, but rather a guide on how to build an individualized plan that includes critical components that are key for success. It breaks the process down into manageable steps that are presented in an order that maximizes efficiency and includes important points to consider for each step. It encourages the user to tailor the protocol to their own unique needs. Discussion: By sharing a framework based on our own best practices and lessons learned, we hope to make it easier for other hospitals to create MCI protocols and to open a dialogue with hospitals that have additional or differing opinions to share. Most importantly, we hope to inspire hospitals to work together as we race to prepare for worst-case scenarios of increasing magnitude.